Hubungan Dukungan Keluarga Dengan Pemberian ASI Pada Ibu Post Partum Di Rumah Sakit Umum Daerah Kotamobagu - WARWURU, PRICILYA MARGARETHA; Sibua, Siska; Mokoagow, Novia (Coping: Community of Publishing in Nursing; Vol 9 No 1 (2021): Februari 2021DO - 10.24843/coping.2021.v09.i01.p08, 2021)
Abstract Breast Milk (ASI) is given directly by the mother to the baby without going through the ASI. Breast Milk also has the content as an antibody that can protect baby from various diseases. The impact happened of hospital general Kotamobagu about family support mother also breastfeeding becomes an obstacle in success of breastfeeding to her baby. The aim of this study is to know and giving breast milk to postpartum mothers of hospital general Kotamobagu. Kind of research is analytic descriptive by using the approach cross sectional that is to looking for relationship between independent and dependent variables, sampling technique that is accidental sampling a sample of 32 respondents includ in the research criteria. Statistical test results by using chi-squere (X 2 ) at the level of significance (?: 0.05) the results obtained p value = 0,000 means that Ho is rejected, so the conclusion is that there is a significant relationship between the relationship of family support with breastfeeding at Kotamobagu Regional General Hospital. That is, there is a relationship between family support and breastfeeding in post partum mothers at Kotamobagu Regional General Hospital. Keywords: family support, breastfeeding, postpartum